Bacillus thuringiensis-derived Cry5B has potent anthelmintic activity against Ascaris suum. - Joseph F Urban; Yan Hu; Melanie M Miller; Ulrike Scheib; Ying Y Yiu; Raffi V Aroian (Public Library of Science (PLoS), 2013)
Ascaris suum and Ascaris lumbricoides are two closely related geo-helminth parasites that ubiquitously infect pigs and humans, respectively. Ascaris suum infection in pigs is considered a good model for A. lumbricoides infection in humans because of a similar biology and tissue migration to the intestines. Ascaris lumbricoides infections in children are associated with malnutrition, growth and cognitive stunting, immune defects, and, in extreme cases, life-threatening blockage of the digestive tract and aberrant migration into the bile duct and peritoneum. Similar effects can be seen with A. suum infections in pigs related to poor feed efficiency and performance. New strategies to control Ascaris infections are needed largely due to reduced treatment efficacies of current anthelmintics in the field, the threat of resistance development, and the general lack of new drug development for intestinal soil-transmitted helminths for humans and animals. Here we demonstrate for the first time that A. suum expresses the receptors for Bacillus thuringiensis crystal protein and novel anthelmintic Cry5B, which has been previously shown to intoxicate hookworms and which belongs to a class of proteins considered non-toxic to vertebrates. Cry5B is able to intoxicate A. suum larvae and adults and triggers the activation of the p38 mitogen-activated protein kinase pathway similar to that observed with other nematodes. Most importantly, two moderate doses of 20 mg/kg body weight (143 nM/kg) of Cry5B resulted in a near complete cure of intestinal A. suum infections in pigs. Taken together, these results demonstrate the excellent potential of Cry5B to treat Ascaris infections in pigs and in humans and for Cry5B to work effectively in the human gastrointestinal tract.